Performance following a first professional concussion among National Basketball Association players - Yengo-Kahn, A. M.; Zuckerman, S. L.; Stotts, J.; Zalneraitis, B. H.; Gardner, R. M.; Kerr, Z. Y.; Solomon, G. S. (The Physician and Sportsmedicine, 2016)
Objectives: Basketball is a physical game played on a hardwood floor among high-jumping athletes at risk for injury. It is currently unknown how sport-related concussion (SRC) affects player performance after injury among professional basketball players. The objective of this study was to explore the impact of SRC on basketball performance among National Basketball Association (NBA) players.